Outpatient Versus Inpatient Total Joint Arthroplasty: Do Medically and Socially Complex Patients Require More Resources but Achieve Similar Outcomes? - Justin Leal, BS; Christine J. Wu, MD; Niall H. Cochrane, MD; Thorsten M. Seyler, MD, PhD; William A. Jiranek, MD; Samuel S. Wellman, MD; Michael P. Bolognesi, MD; Sean P. Ryan, MD (Arthroplasty Today)
Background: This study compared outcomes between patients undergoing outpatient total joint arthroplasty (TJA) at an ambulatory surgery center (ASC) versus a cohort of medically and socially complex patients undergoing TJA at a tertiary healthcare system. Methods: An institutional database at a single academic center was retrospectively reviewed for patients who underwent primary TJA since the opening of an ASC from August 2021 to January 2024. A total of 716 (outpatient: 374; inpatient: 342) total knee arthroplasties and 458 (outpatient: 196; inpatient: 262) total hip arthroplasties met inclusion criteria. Results: Patients in the inpatient total knee arthroplasty group had a higher proportion of patients requiring an emergency department visit (11.4% vs 4.5%; P = .008) and admission (6.7% vs 2.7%; P = .025) within the first 90 days after surgery than the outpatient group; however, 2-year revision-free (97.9% vs 97.9%; P = .75) survival was similar between groups. Patients in the inpatient total hip arthroplasty group had a higher proportion of patients requiring an emergency department visit (13.0% vs 4.6%; P = .035) and admission (7.3% vs 1.0%; P = .018) within the first 90 days after surgery compared to the outpatient group; however, there was no difference in 2-year revision-free survival (96.4% vs 99.5%; P = .059). Conclusions: Medically and socially complex patients undergoing TJA required additional resources during the 90-day postoperative window; however, they achieved similar survivorship as patients who met criteria for outpatient surgery.